Analysis of factors affecting the engagement of pharmacists with the organization working in public health facilities: a quantitative study in Vietnam - Huong V.T.M; Hung N.P; Minh N.T.T; Minh T.N; Duyen L.T.N; Vinh N.P; Chau T.N.N; Anh N.V; Quynh H.T.T; Quoc L.M (BMC Health Services Research)
Abstract Background Pharmacists are among the most crucial resources, playing a pivotal role in the establishment and growth of any medical organization. Therefore, the engagement of pharmacists with the organization is an important factor that influences the stability and development of medical organizations in general and public medical facilities in particular. Objective The study aims to analyze the factors affecting the engagement of pharmacists working in public health facilities in the Mekong Delta with their organizations. Methods The data for this study were collected either through a pre-designed set of questions or via a Google Form distributed to pharmacists working in public health facilities. Results Three out of forty variables were eliminated after conducting the Cronbach's Alpha test. The Kaiser–Meyer–Olkin (KMO) coefficient, ranging from 0.91 to 0.972, indicated that the data were statistically significant and met the criteria for Exploratory Factor Analysis. The results satisfied the requirements for total variance extracted (> 50%), and the Eigenvalue coefficients were all greater than 1 (ranging from 2.828 to 20.962, p < 0.05). Confirmatory Factor Analysis and Structural Equation Modeling were consistent with market data on factors affecting pharmacist engagement. The analysis revealed that six factors had a positive and statistically significant impact on engagement (p < 0.05), while one factor was eliminated due to its influence level not reaching statistical significance (p > 0.05). Conclusion According to the survey, public medical facilities consistently prioritize the well-being and needs of pharmacists, fostering conditions related to salaries, legal policies, work benefits, etc., to make them feel more integrated into their organization.